Comparison of Reading Habits between Research Scholars and Postgraduate Students of Pondicherry University A Survey - Ramaiah, Chennupati K.; Daimari, Bonty M. (DESIDOC Journal of Library & Information Technology, 2022)
This study examined the reading habits among Research scholars and Postgraduate (PG) students in Pondicherry University. Out of the 13 schools of Pondicherry University, 6 schools were selected for the study based on simple random sampling. The purposes of using the various types of reading materials, the accessibility and the use of the Internet and online reading materials and the problems faced while reading were looked at in this study. The survey method and questionnaire tool are used in conducting this study. The findings highlighted some of the factors related to reading habits and interest in Pondicherry University. The study is expected to stimulate further in-depth studies that may help improve reading habits and interests and increase the value of the Central library of Pondicherry University. The findings also revealed that their reading habits changed after joining the university. Most respondents enjoy reading for pleasure and read 2-3 hours during weekends and 4-6 hours during exam days, preferably during the night. While reading, they took small breaks and their break time varied from 5-20 minutes. The majority of them are reading to gain knowledge, preparing for exams. Most of them also confirmed that their reading certainly impacted their academic performance and helped in their vocabulary, learn new facts, and gaining more knowledge. It is observed that the majority of the Research Scholars and PG Students stated the main reasons that are negatively affecting their reading habits is because of their busy schedule of classes. The majority of the respondents indicated that due to lack of concentration, they are not able to read well.